Comparative study of in-vitro antimicrobial activity and phytochemical composition of Sida cuneifolia fruits, leaves, and stem bark extracts - Nalubega, Rebecca; Nyanzi, Steven A.; Nakavuma, Jesca L. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Sida cuneifolia plant parts are important in ethno-veterinary medicine, but no studies exist on a comparative evaluation of phytochemical composition and antimicrobial properties of fruits, stem bark and leaves. This study evaluated and compared extraction yields, phytochemical composition as well as antibacterial and antifungal properties of ether, methanol and aqueous crude extracts of fruits, leaves, and stem bark of S. cuneifolia. Methods: Yields of extracts were determined, and qualitative phytochemical screening tests were carried out to establish their composition. Crude extracts were screened against five bacteria and two fungi. Agar disk diffusion technique was used to determine the inhibition zone diameters. Broth micro-dilution method was used to determine the minimum inhibition concentrations (MIC) and minimum bactericidal concentrations (MBC). Results: Triterpene aglycones, sterols, tannins, athracene derivatives, polyuronides and glucides were found in intense mounts in S. cuneifolia fruits. Leaves contained intense amounts of carotenoids, tannins, polyuronides and coumarin derivatives. For the leaves, methanol extracts had MICs and MBCs as low as (≤3.13 mg/ml) against the majority (6/7) microorganisms hence had the best activity. Considering the stem bark, the ether extracts had the best antimicrobial activity with MICs as low as ≤3.13 mg/ml against 6/7 microorganisms. For the fruits, the ether extracts had the best antibacterial activity with MICs and MBCs as low as (≤3.13 mg/ml) against all tested bacteria. Conclusion: The study provides scientific evidence for ethno-veterinary use of S. cuneifolia leaves, fruits and stem bark, and this can be exploited in the transformative development of ethno-medicine.